Chemical and Biological Studies of Cyperus alternifolius Flowers Essential Oil - H. Ahmed, Amal (Asian Journal of Chemistry, 2012)
The hydro-distilled volatile oil of the flowers of Cyperus alternifolius (Family: Cyperaceae) was analyzed using GC and GC/MS for the first time. Forty compounds representing ca. 98 % of the oil were characterized. Sesquiterpenes constituted the bulk of the oil (ca. 62 %); the major components of the oil were a-cyperone 19.6 %, b-selinene 9.8 %, caryophyllene oxide 7.2 % and cyperene 5.2 %. Antioxidant activity of the volatile oil was tested using a DPPH free radical assay and found to exhibit a significant antioxidant activity.